2003
DOI: 10.1366/000370203322554572
|View full text |Cite
|
Sign up to set email alerts
|

Main Inorganic Component Measurement of Seawater Using Near-Infrared Spectroscopy

Abstract: The potential of near-infrared (NIR) spectroscopy to measure the main inorganic components of seawater as salt-manufacturing materials was investigated. A total of 72 seawater samples collected from six locations was used, and spectra (1100-1800 nm) were acquired by a NIR spectrophotometer with a 1-mm path length. Principal component analysis (PCA), canonical correlation analysis (CCA), and partial least-squares (PLS) regression were performed based on the reference inorganic components. As a result, the princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 8 publications
0
17
0
1
Order By: Relevance
“…The first and second derivative spectra 22,23 were obtained using the Savitsky-Golay method 24 with a segment of 8 points and gap of 0 points. The PLS regression and derivative mathematical treatments were performed using the Unscrambler software.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first and second derivative spectra 22,23 were obtained using the Savitsky-Golay method 24 with a segment of 8 points and gap of 0 points. The PLS regression and derivative mathematical treatments were performed using the Unscrambler software.…”
Section: Discussionmentioning
confidence: 99%
“…The first derivative of the raw spectra is simply a measure of the slope of the spectral curve at every point and the second derivative is a measure of the change in the slope of the curve. The slope of the curve is not affected by baseline offsets in the spectrum, and thus using the first and second derivatives are very effective methods for removing baseline offsets 22,23 . This may be why relatively better results were obtained based on the first or second derivative spectra.…”
Section: Calibration Models For CVmentioning
confidence: 99%
“…The model statistics suggest a poor model only suitable for very rough screening. However previous studies have shown that it is possible to determine inorganic compounds using NIR spectroscopy (Chen et al, 2003). The first three loading in the model (Fig.…”
Section: Prediction Of Ash Contentmentioning
confidence: 99%
“…The first-and secondderivative spectra (Duckworth 2004;Chen et al 2003Chen et al , 2004 were obtained by the Savitsky-Golay method (Madden 1978) with a segment of 20 nm and a gap of 0 nm. The PLS regression and derivative mathematical treatments were carried out using the Unscrambler Ver.7.6 software.…”
Section: Discussionmentioning
confidence: 99%